Integrating context-aware public displays into a mobile hospital information system. - Favela, J.
Hospitals are convenient settings for deployment of ubiquitous computing technology. Not only are they technology-rich environments, but their workers experience a high level of mobility resulting in information infrastructures with artifacts distributed throughout the premises. Hospital information systems (HISs) that provide access to electronic patient records are a step in the direction of providing accurate and timely information to hospital staff in support of adequate decision-making. This has motivated the introduction of mobile computing technology in hospitals based on designs which respond to their particular conditions and demands. Among those conditions is the fact that worker mobility does not exclude the need for having shared information artifacts at particular locations. In this paper, we extend a handheld-based mobile HIS with ubiquitous computing technology and describe how public displays are integrated with handheld and the services offered by these devices. Public displays become aware of the presence of physicians and nurses in their vicinity and adapt to provide users with personalized, relevant information. An agent-based architecture allows the integration of proactive components that offer information relevant to the case at hand, either from medical guidelines or previous similar cases.
Keywords: Agent-based architecture; Autonomous agents; Context-aware computing; Context-aware public display; Decision-making.; Electronic patient record; Mobile computing; Mobile hospital information system; Ubiquitous computing